Ghana's transformation - Kufuor, John Agyekum (International Food Policy Research Institute, 2011)
The first decade of the new millennium brought significant positive change to Ghana. Hunger was cut in half and Ghanaians exercised increasing democratic freedom, making the country one of the most improved and politically stable in Africa. John Kufuor served as the democratically elected president of the Republic of Ghana from 2001–09, and his administration helped to initiate or continue improvements in farming, nutrition, education, healthcare, and infrastructure. In “Ghana’s Transformation,” Kufuor gives a first-person account of his years as president, describing some of his administration’s most successful projects, especially those related to agriculture. In one example, Ghanaian farmers, who make up about 60 percent of the country’s population, were taught to use best practices, including irrigation and fertilization, to increase yields. Cocoa production doubled as a result, and the government was also able to use locally grown food to provide school children with a healthy daily meal. Kufuor describes food security as the catalyst for improving an economy and instituting democracy. “Food is the most basic of needs,” he writes. “It decides not just the health of individuals but also the health of communities.”